Packaging Audio Visual Media in Tatak Tintoa Serser in Learning of Dairi Dance - Sitti Rahmah; Yusnizar; Tuti Rahayu (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
Tatak Tintoa Serser is one of the traditional dances of the Pakpak Dairi community which illustrates the mutual cooperation attitude in the lives of farmers in farming. Tatak is a term used to refer to dance to the Pakpak Dairi community. This study focuses on the preparation of instructional media in the form of VCDs from the Serser Tintoa Tatak which is closely related to the social understanding of the Dairi community. The objectives of this study are (1) Identifying the artistic structure of dance as outlined in the show (2) Arranging dance learning media in the form of VCD. This study uses a qualitative approach, by conducting interviews with informants (artists, art practitioners, community leaders, academics) because it deals with meaning and context, data collection and analysis that take place simultaneously. The program, with research subject Tatak Tintoa Serser, which is packaged in the form of Audio Visual, the research sample is Dance Education Study Program students who are used as models in making media. This research produces a VCD media product that contains the techniques of motion in the Tatak Tintoa Serser, terms in motion, and the meaning of dance that can be a source of learning in learning Dairi Dance. Product validation is carried out by media expert validation and material expert validation which shows the product's feasibility, and has been tested with Dance Education Study Program students in the Pakpak Dairi Dance course TA 2018/2019